The analysis of the determinants of sovereign credit ratings : evidence from SADC countries - Dakalo, Priviledge Netswera (My University, 2021)
The main aim of the study is to analyze determinants of sovereign credit ratings (SCRs) for Southern African Development Community (SADC) countries, namely Angola, Botswana, Mozambique, South Africa and Zambia. The analysis is based on the SCRs given by Standard and Poor’s (S&P). The selected explanatory variables are gross domestic product (GDP) per capita, inflation, external debt, foreign direct investment (FDI) inflows and control of corruption for the period 1990-2016, based on annual data. The panel root test results, namely IPS, LLC, ADF Fisher and PP Fisher, show that GDP per capita, external debt and FDI are stationary at 5% level of significance. The Hausman test results indicates that the identified explanatory variable explains 80% of SCRs. The model observed a positive relationship between SCR, inflation and control of corruption. It also observed a negative correlation between SCR, GDP per capita, external debt and FDI. The Pedroni residual cointegration test results indicate that there is no long-run relationship among variables and no autocorrelation as shown by serial correlation LM test results. The study recommends that the selected member states of SADC develop strategic plans for reducing budget deficits. This will help countries to manage their debts, especially foreign currency denoted debt and to attract foreign investment. Keywords: Sovereign credit ratings, fixed effects model, random effects, Hausman test.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2021
Keywords: Sovereign credit ratings; Fixed effects model; Random effects; Hausman test; Credit ratings; Gross domestic product; Inflation (Finance); Debts, External; Investments, Foreign